Level of Consumer Understanding of BPOM Labeling on Skintific Skincare Products Based on Islamic Compliance (Study of Class XII Students of MAN 2 Lamongan) - Nabilatur Rohmah; Syuhada Syuhada; Ahmad Munir Hamid (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
The current development of skincare is accompanied by increasing consumer understanding of the safety of the products used, such as the BPOM label. However, many teenagers do not understand the ingredients in the skincare products they use. Not all skincare products are safe and comply with health standards. Apart from that, many teenagers do not understand compliance in choosing treatments with Islamic law, such as developing with ethical ingredients, identifying haram (prohibited) ingredients, protecting products in an ethical manner and in accordance with Islamic Compliance. This research aims to determine the level of understanding of class XII MAN 2 Lamongan female students regarding the BPOM label on skintific skincare products and to determine the level of understanding of class The method used in this research uses a qualitative approach. Primary data collection techniques through interviews, observation and documentation. The data analysis used is data collection, data reduction, data presentation and conclusions.The results of the research show that the level of female students' understanding of BPOM labels is very high, as for the implementation carried out such as checking BPOM labels on skintific products on various sales platforms in advance, they are also able to utilize existing sites to search for more detailed information regarding the importance of understanding labels. BPOM. Apart from that, the understanding of class , mercury, and pork.